Injectable Mussel‐Inspired highly adhesive hydrogel with exosomes for endogenous cell recruitment and cartilage defect regeneration - Zhang, Fang-Xue; Liu, Peng; Ding, Wang; Meng, Qing-Bing; Su, Di-Han; Zhang, Qi-Chen; Lian, Rui-Xian; Yu, Bao-Qing; Zhao, Ming-Dong; Dong, Jian; Li, Yu-Lin; Jiang, Li-Bo (Biomaterials, 2021)
In the early stage of osteoarthritis (OA), cartilage degradation in the surface region leads to superficial cartilage defect. However, enhancing the regeneration of cartilage defect remains a great challenge for existing hydrogel technology because of the weak adhesion to wet tissue. In the present study, an injectable mussel-inspired highly adhesive hydrogel with exosomes was investigated for endogenous cell recruitment and cartilage defect regeneration. The hydrogel with high bonding strength to the wet surface was prepared using a crosslinked network of alginate-dopamine, chondroitin sulfate, and regenerated silk fibroin (AD/CS/RSF). Compared with commercial enbucrilate tissue adhesive, the AD/CS/RSF hydrogel provided a comparative lap shear strength of 120 kPa, with a similar gelation time and a higher capacity for maintaining adhesive strength. The AD/CS/RSF/EXO hydrogel with encapsulated exosomes recruited BMSCs migration and inflation, promoted BMSCs proliferation and differentiation. Most importantly, the AD/CS/RSF/EXO hydrogel accelerated cartilage defect regeneration in situ, and extracellular matrix remodeling after injection in rat patellar grooves. The exosomes released by the hydrogels could recruit BMSCs into the hydrogel and neo-cartilage via the chemokine signaling pathway. Our findings reveal an injectable and adhesive hydrogel for superficial cartilage regeneration, which is a promising approach for minimally treating cartilage defect with arthroscopic assistance.